Distilling the Essence of the McKinsey* Way: The Problem-Solving Cycle. (December 2019) - Chia, Austin
Consulting projects where students are tasked to propose solutions to a client issue are a common feature in many business courses. Whether scenario-based or dealing with real clients, students engaged in consulting tasks tend to focus on solution development without giving due consideration to the underlying process by which they derive their solutions. Drawing on consulting practitioner approaches, this article presents a translation of the McKinsey approach as a six-stage structured problem-solving methodology that can be used to guide students on how to develop solutions in a systematic, logical, and evidence-based way. Prescribing a standardized methodology to students to guide their approach to consulting tasks ensures that they are able define and decompose business problems effectively and enhances the credibility of their proposed solutions.